Localized lentivirus delivery via peptide interactions. Issue 9 (6th March 2016) - Skoumal, Michael; Seidlits, Stephanie; Shin, Seungjin; Shea, Lonnie
ABSTRACT: Gene delivery from biomaterial scaffolds has been employed to induce the expression of tissue inductive factors for applications in regenerative medicine. The delivery of viral vectors has been described as reflecting a balance between vector retention and release. Herein, we investigated the design of hydrogels in order to retain the vector at the material in order to enhance transgene expression. Poly(ethylene‐glycol) (PEG) hydrogels were modified with poly‐l ‐lysine (PLL) to non‐covalently bind lentivirus. For cells cultured on the hydrogels, increasing the PLL molecular weight from 1 to 70 kDa led to increased transgene expression. The incubation time of the virus with the hydrogel and the PLL concentration modulated the extent of virus adsorption, and adsorbed virus had a 20% increase in the half‐life at 37°C. Alternatives to high molecular weight PLL were identified through phage display technology, with peptide sequences specific for the VSV‐G ectodomain, an envelope protein pseudotyped on the virus. These affinity peptides could easily be incorporated into the hydrogel, and expression was increased 20‐fold relative to control peptide, and comparable to levels observed with the high molecular weight PLL. The modification of hydrogels with affinity proteins or peptides to bind lentivirus can be a powerful strategy to enhance and localized transgene expression. Biotechnol. Bioeng. 2016;113: 2033–2040. © 2016 Wiley Periodicals, Inc. Abstract : By conjugating affinity peptides to poly(ethylene‐glycol) (PEG) hydrogels, lentiviral vectors were non‐covalently bound to the hydrogel surface. Poly‐l ‐lysine (PLL) and short, 12‐amino acid sequences identified via phage display, were analyzed. The modification of hydrogels with affinity proteins or peptides to bind lentivirus can be a powerful strategy to enhance and localized transgene expression.